Eating Food. Invitation to the House (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article will discuss the sociolinguistic and cultural aspects of food-related invitations with a particular focus on the expression "inviting someone to the house and eat" as a complex linguistic and pragmatic construct. Food and welcoming guests into the home are common practices in all societies as a sign of hospitality, socialization, and ethnicity. Although it is common, the linguistic representation of such invitations is quite different across languages and cultural backgrounds, and it is therefore an interesting topic in cross-cultural analysis. Although much has been said about hospitality discourse, little has been said about food-based invitations, especially in terms of how they serve as indicators of social status, courtesy, and repayment in the cultural context. The present research is based on the qualitative discourse analysis comprising ethnolinguistic comparisons and the analysis of spoken and written sources, which are based on real-life conversations, folk stories, and cultural life. As the analysis shows, food-related invitations are not merely a sign of courtesy but also a sign that a particular culture is generous, reflects feelings, and belongs to a social group. Any rejection or acceptance of such invitations has more social implications, which are frequently related to the notions of respect, obligation, and relationship interactions. The results indicate that food-invitation discourse is a connecting element between material sustenance and symbolic representations of social respect and relation-making. The study has made a contribution to sociopragmatics research due to the understanding of the connection between language and food, as well as social identity as revealed in language choices related to food-related invitations, which supports the need to extend the investigation into the relationship between language, food, and social identity in different cultures.